Assessment of cerebral blood perfusion changes after neurorehabilitation therapy in patients with middle cerebral artery infarction: An acetazolamide‐challenged SPECT study. Issue 1 (11th November 2017) - Jang, Kyung‐Sool; Im, Jooyeon J.; Chung, Yong‐An; Chung, Sung‐Woo; Jeong, Hyeonseok S.; Kim, Min‐Wook
Abstract: Stroke is a leading cause of death and disability worldwide. Although neuroimaging has been used to examine brain changes related to recovery from stroke, cerebral perfusion changes after rehabilitation have yet to be elucidated. The aim of this study was to evaluate the regional cerebral blood flow (rCBF) changes and their associations with gross motor functions after neurorehabilitation therapy in stroke patients. A total of 7 patients with middle cerebral artery (MCA) infarction received conventional neurorehabilitation therapy twice per day for 4‐6 weeks on admission. Brain perfusion images were acquired before and after the therapy using acetazolamide‐challenged single photon emission computed tomography. A whole‐brain voxel‐wise analysis found increased rCBF in the contralesional prefrontal, precentral, and postcentral cortical areas and decreased rCBF in the ipsilesional insula, posterior orbital gyrus, and central operculum. Moreover, a region of interest analysis revealed that rCBF of the ipsilesional basal ganglia was positively correlated with motor function at baseline and follow‐up, and perfusion changes in the ipsilesional basal ganglia was positively correlated with changes in motor function. These findings suggest that the contralesional prefrontal and sensorimotor cortex may play compensatory roles during the motor recovery and that perfusion in the ipsilesional basal ganglia is closely associated not only with current functional status but also with clinical improvement after neurorehabilitation therapy in patients with MCA infarction. Further studies with larger sample size are warranted to investigate whether assessment of cerebral perfusion may be clinically useful in rehabilitation of stroke patients.